2020
DOI: 10.1002/ep.13411
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium‐based metal–organic framework for removal of dye from aqueous solution

Abstract: Metal–organic framework ([Cd2(oba)2(4‐bpdb)2] n·3.5(DMF)) (TMU‐8) was successfully synthesized via mechanosynthesis by using nonlinear dicarboxylate and linear N‐donor. The TMU‐8 exhibited accessible cages and tunnels, specific adsorption making it excellent adsorbent for dye removal. The obtained TMU‐8 exhibited accessible cages and tunnels, specific adsorption making them excellent adsorbent for dye removal. The adsorption isotherms, kinetics, thermodynamics, and spectroscopic analyses of the removal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Hazrati et al [93] synthesized TMU-8 with the solvothermal method and applied it to remove reactive black 5 (RB5) dye from the aquatic environment. The maximum capacity obtained was 79.36 mg/g for the RB5 adsorption.…”
Section: Other Types Of Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hazrati et al [93] synthesized TMU-8 with the solvothermal method and applied it to remove reactive black 5 (RB5) dye from the aquatic environment. The maximum capacity obtained was 79.36 mg/g for the RB5 adsorption.…”
Section: Other Types Of Mofsmentioning
confidence: 99%
“…Over time, active sites of adsorbent are occupied by dye molecules and the adsorbent can no longer adsorb more dyes, whereby the adsorption process stops [192,193]. Most MOFs need a very short time to reach the equilibrium point of adsorption [86,89,92,93,95,184]. Fast adsorption may be due to various interactions between MOF and contaminant molecules.…”
Section: The Effect Of Contact Time On Dye Removal Using Mofsmentioning
confidence: 99%
“…161 Safari et al have shown that the adsorption of dye on a MOF in wastewater may be due to p-p stacking between the ligand of the MOF and the arene part of the dye molecule. 161 p-p Stacking is also observed between the aromatic part of imidazole rings in ZIF-8 (MOF) and the arene part of the malachite green, resulting in higher adsorption efficiency of MG with ZIF-8. 111 There are few reports on the hydrogen bonding mechanisms between MOFs and dyes.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…29 MOFs have attractive structural properties such as low framework densities, uniformly structured nanoscale cavities, accessible cages, high surface area, tunnels and modifiable pores, good chemical resistance and specific adsorption affinities make MOFs attractive materials for sorbents of pollutants. 30,31 Up to date, there are large numbers of reported MOFs and some of them have been studied for liquid adsorption. [32][33][34] However, most MOF materials suffer from insufficient aqueous stability, mainly over a broad range of pH values.…”
Section: Introductionmentioning
confidence: 99%